Prostanoids and Resolution of Inflammation – Beyond the Lipid-Mediator Class Switch - Schmid, Tobias; Brüne, Bernhard (Frontiers in Immunology, 2021)
Bioactive lipid mediators play a major role in regulating inflammatory processes. Herein, early pro-inflammatory phases are characterized and regulated by prostanoids and leukotrienes, whereas specialized pro-resolving mediators (SPM), including lipoxins, resolvins, protectins, and maresins, dominate during the resolution phase. While pro-inflammatory properties of prostanoids have been studied extensively, their impact on later phases of the inflammatory process has been attributed mainly to their ability to initiate the lipid-mediator class switch towards SPM. Yet, there is accumulating evidence that prostanoids directly contribute to the resolution of inflammation and return to homeostasis. In this mini review, we summarize the current knowledge of the resolution-regulatory properties of prostanoids and discuss potential implications for anti-inflammatory, prostanoid-targeted therapeutic interventions.